Multilevel Interactions of Stress and Circadian System: Implications for Traumatic Stress - Agorastos, Agorastos; Nicolaides, Nicolas C.; Bozikas, Vasilios P.; Chrousos, George P.; Pervanidou, Panagiota (Frontiers in Psychiatry, 2020)
The dramatic fluctuations in energy demands by the rhythmic succession of night and day on our planet has prompted a geophysical evolutionary need for biological temporal organization across phylogeny. The intrinsic circadian timing system (CS), represents a highly conserved and sophisticated internal “clock”, adjusted to the 24-hour rotation period of the earth, enabling a nyctohemeral coordination of numerous physiologic processes, from gene expression to behavior. The human CS is tightly and bidirectionally interconnected to the stress system (SS). Both systems are fundamental for survival and regulate each other’s activity in order to prepare the organism for the anticipated cyclic challenges. Thereby, the understanding of the temporal relationship between stressors and stress responses is critical for the comprehension of the molecular-basis of physiology and pathogenesis of disease. A critical loss of the harmonious timed order at different organizational levels may affect the fundamental properties of neuroendocrine, immune and autonomic systems, leading to a breakdown of biobehavioral adaptative mechanisms with increased stress sensitivity and vulnerability. In this review, following an overview of the functional components of the SS and CS, we present their multilevel interactions and discuss how traumatic stress can alter the interplay between the two systems. Circadian dysregulation after traumatic stress exposure may represent a core feature of trauma-related disorders mediating enduring neurobiological correlates of trauma through maladaptive stress regulation. Understanding the mechanisms susceptible to circadian dysregulation and their role in stress-related disorders could provide new insights into disease mechanisms, advancing psychochronobiological treatment possibilities and preventive strategies in stress-exposed populations.